Blood and urinary concentrations of Salbutamol in asthmatic subjects - Elers, J.; Pedersen, L.; Henninge, J.; Lund, T. K.; Hemmersbach, P.; Dalhoff, K.; Backer, V. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Data on blood and urinary concentrations of salbutamol after inhalation and oral administration in healthy subjects are scarce. Accordingly, we examined the pharmacokinetics of inhaled and oral salbutamol in asthmatic subjects.